"Jammu, Kashmir and Ladhak" - "Dewan, Parvez" (New Delhi, 2004)
A comprehensive volume containing almost everything that a reader might want to know about Kashmir: its art, history, culture and society, as well as trekking routes and tourist places. Profusely illustrated in colour and with maps, it is a handy reference work which touches almost all frequently asked questions about this beautiful Himalayan state of North India.
Keywords: Jammu & Kashmir-History